光学设备 (2025)
[问题]为了抑制与波长滤波器的插入/移除和类型相对应的光学性能的劣化。[解决手段]一种光学设备(200)，包括：处理部件(203、208)，其被配置为在能够插入或移除波长滤波器(201)的情况下进行与摄像有关的处理，所述波长滤波器(201)被配置为控制入射到图像传感器(202)上的摄像光的波长，所述图像传感器(202)被配置为拍摄由光学系统(101)形成的被摄体图像；以及获取部件(208)，其被配置为获取用于所述处理的关于所述光学系统的光学信息，所述光学信息对应于与所述波长滤波器的插入/移除和类型中的至少一者相对应的摄像光的波长。 [Problem] To prevent a drop in optical performance caused by the insertion/removal or type of a wavelength filter. [Solution] Provided is an optical device 200 including: processing means 203, 208 that perform processing related to imaging in cases in which it is possible to insert/remove a wavelength filter 201 that controls the wavelength of imaging light entering an imaging element 202 when using the imaging element to image a subject image formed by an optical system 101; and an acquisition means 208 that acquires optical information of the optical system, said optical information being used in the processing and corresponding to the wavelength of imaging light according to at least one of the insertion/removal and the type of the wavelength